2019
DOI: 10.1093/ajcp/aqz146
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Rapid On-Site Evaluation and Final Cytologic Diagnosis in Patients Undergoing Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration for Non-Small Cell Lung Cancer Staging

Abstract: Objectives In patients with lung cancer undergoing mediastinal staging through endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), decisions are based on rapid on-site evaluation (ROSE) findings. We aimed to analyze the concordance rate between ROSE diagnosis and final diagnosis. Methods A prospective study was carried out in patients undergoing EBUS-TBNA for lung cancer staging. Diagnosis concordanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The study by Stevenson et al a showed an increase in diagnostic yield within the first six years of seven years of ROSE practice [ 42 ]. This is supported by higher concordance rates between ROSE and final diagnosis reported by Caupena and colleagues (96.1%) in 637 lymph node samples obtained via EBUS-TBNA during that year compared to older publications [ 43 ].…”
Section: Rapid On-site Evaluationsupporting
confidence: 64%
“…The study by Stevenson et al a showed an increase in diagnostic yield within the first six years of seven years of ROSE practice [ 42 ]. This is supported by higher concordance rates between ROSE and final diagnosis reported by Caupena and colleagues (96.1%) in 637 lymph node samples obtained via EBUS-TBNA during that year compared to older publications [ 43 ].…”
Section: Rapid On-site Evaluationsupporting
confidence: 64%
“…In fact, several studies investigated the contribution of ROSE to the adequacy of sampling for lung cancer diagnosis during EBUS-TBNA, with contradictory results ( 2 , 6 , 15 , 35 , 40 ). Some of the trials reported a significant contribution of ROSE to the diagnosis and staging of lung cancer and a high concordance between ROSE and the final diagnosis ( 6 , 41 ).On the contrary, randomized trials failed in finding differences in diagnostic yield when EBUS-TBNA is performed with or without the use of ROSE ( 33 , 34 , 42 ).…”
Section: The Impact Of Rose In Diagnosis Staging and Molecular Profiling Of Lung Cancermentioning
confidence: 99%
“…As discussed by Caupena et al , the absence of differences in the duration of the procedures may be due to a reduction of the number of sampled nodes and passes per target associated with the use of ROSE. In fact, when following ROSE a diagnosis of positive N3 node is reached, no further sampling on N2/N1 sampling has necessarily to be performed ( 41 ). Moreover, without ROSE a minimum of three passes per target is advised ( 44 ), while the use of ROSE may allow to reduce the number of biopsies required to obtain diagnosis ( 35 ).…”
Section: The Impact Of Rose In Diagnosis Staging and Molecular Profiling Of Lung Cancermentioning
confidence: 99%
“…The latter approach facilitates rapid onsite evaluation (ROSE), whereby direct slides are rapidly stained and evaluated in real‐time in the endoscopy suite for adequacy and the presence of diagnostic material 5‐7 …”
Section: Introductionmentioning
confidence: 99%